Genetic Information: Comparing Alternative Regulatory Approaches when Prevention Matters - Francesca Barigozzi; Dominique Henriet (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
We compare the alternative approaches for regulating genetic information in the health insurance market when prevention measures are available. In the model, firms offer insurance contracts to consumers who are initially uninformed of their risk type but can obtain such information by performing a costless genetic test. A crucial ingredient of our analysis is that information has decision-making value since it allows for optimal choice of a self-insurance action (secondary prevention). We focus on the welfare properties of market equilibria obtained under the different regulatory schemes and, by using an intuitive graphical analysis, we rank them unambiguously. Our results show that Disclosure Duty weakly dominates the other regulatory schemes and that Strict Prohibition represents the worst regulatory approach.
Keywords: 330; Krankenversicherung; Gesundheitsvorsorge; Gesundheitspolitik; Genetik; Selbstversicherung; Theorie